Evaluating structural failure probability during aftershocks based on spatiotemporal simulation of the regional earthquake sequence. (15th January 2023) - Pu, Wuchuan; Li, Yuanhui
Highlights: The ETAS model was used to simulate and evaluate the aftershock hazard. A framework was proposed to assess failure probability of structure under aftershocks. The aftershock demand of structure varying with time was investigated. Abstract: Engineering structures damaged in a mainshock become much more vulnerable to the subsequent aftershocks. Estimating the aftershock hazard and the subsequent structural fragility is of significant interest for post-mainshock decision-making. This study introduced the spatiotemporal epidemic-type aftershock sequence (ETAS) model to simulate the regional aftershock sequence and developed a framework for evaluating the aftershock-induced failure probability of structures. The procedure includes: aftershock sequence modeling, aftershock hazard estimation, aftershock ground motion generation, fragility analysis, and structural damage probability estimation. The procedure can quantitatively estimate the failure probability of a mainshock-damaged structure during aftershocks considering the influence of spatial location of aftershock and time interval between the mainshock and aftershock. As an example, the 2021 Yangbi earthquake sequence was fitted by the ETAS model, and the failure probability of a local 5-story concrete frame structure was analyzed. The variation of the failure probability of the structure with the increase of time was investigated.